2003
DOI: 10.1097/01.brs.0000086822.76638.76
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Field-Based Image-Guided Spine Surgery Part Two: Results of a Cadaveric Study Evaluating Thoracic Pedicle Screw Placement

Abstract: Our study has shown that EMF image-guided thoracic pedicle screw placement results in a similar incidence of safely placed screws as does conventional fluoroscopy. When set-up time and image-capture time were factored in for image guidance, the average time to insert a pedicle screw was equal for both techniques. The use of EMF image guidance significantly reduced fluoroscopic time and thus radiation exposure per screw compared with conventional fluoroscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 15 publications
0
34
1
Order By: Relevance
“…Five in vitro papers also revealed that 2D FluoroNav obtained a lesser, but insignificant, perforation risk compared with the conventional methods (Fig. 1) [39,[41][42][43]54].…”
Section: Two-dimension Fluoroscopy-based Navigation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Five in vitro papers also revealed that 2D FluoroNav obtained a lesser, but insignificant, perforation risk compared with the conventional methods (Fig. 1) [39,[41][42][43]54].…”
Section: Two-dimension Fluoroscopy-based Navigation Systemmentioning
confidence: 99%
“…FluoroNav that does not require registration might reduce surgical time. However, some authors pointed out that extra time was needed for the setup of the system, placing the transmitter and acquiring suitable images for navigation, which would not significantly reduce the total insertion time per screw [15,17,[41][42][43].…”
Section: Other Perioperative Findingsmentioning
confidence: 99%
“…3,4 More recently, Sagi et al, in a cadaveric study comparing electromagnetic fi eld-based (EM) image guidance to conventional anatomical/fl uoroscopic guidance, found similar rates of screw misplacement in the thoracic spine. 5 EM tracking, as an alternative to optical tracking, signifi cantly reduced mean screw insertion time per screw (179 versus 261 seconds, P = .007) and mean total fl uoroscopy time (162 versus 261 seconds, P = .045). 5 Thus, EM tracking technology, which, unlike optical imaging, does not depend on continuous line-ofsight registration, represents an important development in the advance of image-guided complex spine surgery.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…Previous studies evaluating thoracic placement have focused mostly in the lower thoracic region [1,4,12,16,17,19,26,29]. Furthermore, accuracy of thoracic pedicle screw instrumentation has been reported in several cadaveric populations [5,7,21,22,25,28,29,31,32], and with the use of assisted-navigation techniques [2,5,6,8,25]. While there is data on thoracic screw placement accuracy in the literature, we found little information specifically reporting on upper thoracic screws inserted in vivo on nondeformed spines.…”
Section: Discussionmentioning
confidence: 89%